Cranium morphometry for distinguishing male and female Muscovy duck (Cairina moschata) before sexual maturity - Mafatichul Firdaus; Abdul Samik; Yeni Dhamayanti; Raden Tatang Santanu Adikara; Hana Eliyani; Soeharsono Soeharsono (Universitas Airlangga, 2022)
Gender determination of Muscovy duck as early as possible is essential for the efficiency and effectiveness of duck production. This study aimed to determine the morphometric differences in prepubertal male and female Muscovy duck (Cairina moschata) as predictors of gender. This study used a split-plot design, with the observed variables cranium length, width and height, mandibular length, and rostrum length and width. This study used a total of 80 samples of duck heads consisting of 40 male and 40 female Muscovy duck heads, with ten heads each in the age group of 2, 4, 6, and 8 weeks, respectively. Results showed that the length, width, and height of the cranium, mandibular length, and rostrum lengthand width were greater in males (p <0.05) than those of the females in all age groups. It could be concluded that the morphometric size of prepubertal male Muscovy ducks head was greater than those of the female ones at the same age; thereby, it could be used to distinguish gender. Based on the morphometrics, further study can also be conducted to measure other body parts of the Muscovy duck apart from the cranium. In addition, it is necessary to study the morphometric measurements of the cranium in other poultry as a basis for identifying sex.